STEM-CL investigations on the influence of stacking faults on the optical emission of cubic GaN epilayers and cubic GaN/AlN multi-quantum wells - Kemper, R.M.; Veit, P.; Mietze, C.; Dempewolf, A.; Wecker, T.; Christen, J.; As, D.; Lindner, Jörg

Issues of Automated Software Composition in AI Planning - Mohr, Felix (Proceedings of the 29th International Conference on Automated Software Engineering (ASE))
Automated programming aims at automatically assembling a new software artifact from existing software modules. Although automated programming was revitalized through automated software composition in the last decade, the problem cannot be considered solved. Automated software composition is widely accepted as being a planning task, but the problem is that it has very special properties that other planning problems do not have and that are commonly overseen. These properties usually imply that the composition problem cannot be solved with standard planning tools. This paper gives a brief and intuitive description of the planning problem that most approaches are based on. It points out special properties of this problem and explains why it is not adequate to solve the problem with classical planning tools as done by most existing approaches.

Cubic GaN/AlN multi-quantum wells grown on pre-patterned 3C-SiC/Si (001) - Kemper, R. M.; Mietze, C.; Hiller, L.; Stauden, T.; Pezoldt, J.; Meertens, D.; Luysberg, M.; As, D. J.; Lindner, Jörg (physica status solidi (c))
We report for the first time on the growth of cubic AlN/GaN multi‐quantum wells (MQWs) on pre‐patterned 3C‐SiC/Si (001) substrates. The sample structure consists of 10 periods of 2 nm c‐AlN barriers with a 4 nm c‐GaN layer in between, which were grown on 3C‐SiC post shaped structures by means of molecular beam epitaxy. Substrate patterning has been realized by electron beam lithography and a reactive ion etching process. The 3C‐SiC posts have a length of about 550 nm and a height of about 700 nm. (Scanning) transmission electron microscopy studies show that the morphology of the MQWs is clearly influenced by {111} stacking faults, modulating the local growth rate. Further, the growth at the edges of the surface pattern is investigated. The MQW layers cover the 90° edges by developing low‐index facets rather than by forming a conformal system of 90° angled layers.

Self-organized fabrication of periodic arrays of vertical, ultra-thin nanopillars on GaAs surfaces - Riedl, Thomas; Lindner, Jörg (physica status solidi (a))
This paper presents a low‐cost procedure that allows for self‐organized fabrication of periodically arranged, sub‐50 nm diameter, vertical‐sidewall GaAs nanopillars on GaAs surfaces based on nanosphere lithography, and reactive ion etching (RIE). Monodispersed polystyrene (PS) sphere double layers are deposited from a colloidal suspension on pre‐treated, hydrophilized GaAs substrates. Ni is thermally evaporated to act as a hard mask for subsequent RIE. Scanning electron microscopy reveals that the Ni nanoparticles left on the substrate after PS sphere removal have polygon‐shaped in‐plane cross‐sections corresponding to the shape of the double layer mask openings. RIE using SiCl4 at low pressure and high power density leads to the formation of vertical nanopillars with circular to oval cross‐sections, whose diameters are reduced by ∼1/3 compared to those of the Ni nanoparticles. These findings can be explained by plasma‐enhanced surface diffusion and sputtering processes during RIE. The obtained GaAs nanopillars have an average diameter of only ∼23 nm, exhibit an excellent verticality with a sidewall angle of 88.9 ± 0.4° and planar top faces, as visible in transmission electron microscopy images.

Thermal Modification of Nanoscale Mask Openings in Polystyrene Sphere Layers - Riedl, Thomas; Strake, Matthias; Sievers, Werner; Lindner, Jörg (MRS Proceedings)
An experimental analysis of the morphology changes of hexagonally close packed polystyrene sphere monolayers induced by annealing in air is presented. The triangular interstices between each triple of spheres, which are frequently used as nanoscale mask openings in colloidal lithography, are observed to gradually shrink in size and change in shape upon annealing. Top view scanning electron microscopy images reveal that different stages are involved in the closure of monolayer interstices at annealing temperatures in the range between 110°C and 120°C. In the early stages shrinkage of the triangular interstices is dominated by material transport to and thus shortening of their corners, in the late stages interstice area reduction via displacement of the triangle edges becomes significant. At intermediate annealing times the rate of interstice area reduction displays a maximum before a stabilized state characterized by a rounded isosceles triangular shape forms.

Comparison of Theoretical Approaches Predicting the Coherent-Semicoherent Transition in Nanoscale Axial Heterostructures - Riedl, Thomas; Lindner, Jörg (Symposium YY – Elastic Strain Engineering for Unprecedented Materials Properties)
The formation of misfit dislocations is an important issue for the performance of heteroepitaxial micro- and optoelectronic devices. We analyze three approaches that quantify the stability of misfit dislocations in axial-heteroepitaxial nanowires with respect to applicability and predictions of critical nanowire dimensions. The “nanoheteroepitaxy” approach of Zubia and Hersee proves suitable for determination of strain partitioning in the presence of an elastic mismatch. Concerning the critical thickness and diameter however the descriptions of Ertekin et al. and Glas respectively yield more reliable results, owing to the consideration of the total coherent and dislocation related energies plus the residual strain energy. In contrast to the model of Ertekin et al., which refers to infinitely long nanowires, the other two mentioned approaches allow predictions of the critical thickness of mismatched deposits on the nanowire axial face.

Reliability of high-resolution electron backscatter diffraction determination of strain and rotation variations using phase-only and cross correlation - Riedl, Thomas; Wendrock, H. (Crystal Research and Technology)
This contribution analyzes the reliability of strain and rotation variation determination using cross‐ as well as phase‐only correlation of experimental wide‐angle electron backscatter diffraction (EBSD) patterns. For both rotation and three‐point bending the resulting displacement gradient tensor components are examined in terms of magnitude and statistical scatter as a function of various correlation procedure parameters and signal‐to‐noise ratio. It is shown that on the one hand the Fourier filter width has a major impact on the strain results. At higher noise level a smaller filter width has to be applied for obtaining maximum precision. On the other hand, the influence of the degree of overlap of the regions of interest positioned in the patterns is less important. For both rotation and bending experiments the cross‐correlation variant yields a smaller standard deviation with respect to phase‐only correlation, in particular for elevated noise level. The difference is attributed to the stronger propagation of noise effects in the course of phase‐only correlation function calculation and fitting. In the rotation experiment a standard deviation of ∼1.0 × 10^−4, averaged over the displacement gradient tensor components, and a rotational precision of ∼1.5 × 10^−4 rad have been achieved by using optimized evaluation settings.

Structure and surface chemistry analysis of ultra-thin reactive ion etched GaAs (111) nanopillars - Riedl, Thomas; Kovács, A.; Meertens, D.; Lindner, Jörg

RBS of gold-coated polystyrene nanospheres - Rüsing, M.; Merten, L.; Reinert, P.; Rogalla, D.; Becker, H.-W.; Lindner, Jörg

Integrating Software and Hardware Verification - Jakobs, Marie-Christine; Platzner, Marco; Wiersema, Tobias; Wehrheim, Heike (Proceedings of the 11th International Conference on Integrated Formal Methods (iFM))
Verification of hardware and software usually proceeds separately, software analysis relying on the correctness of processors executing instructions. This assumption is valid as long as the software runs on standard CPUs that have been extensively validated and are in wide use. However, for processors exploiting custom instruction set extensions to meet performance and energy constraints the validation might be less extensive, challenging the correctness assumption.In this paper we present an approach for integrating software analyses with hardware verification, specifically targeting custom instruction set extensions. We propose three different techniques for deriving the properties to be proven for the hardware implementation of a custom instruction in order to support software analyses. The techniques are designed to explore the trade-off between generality and efficiency and span from proving functional equivalence over checking the rules of a particular analysis domain to verifying actual pre and post conditions resulting from program analysis. We demonstrate and compare the three techniques on example programs with custom instructions, using stateof-the-art software and hardware verification techniques.